COVID-19 social and economic disruptions, mental health, and coping behaviours among young Canadians: a structural equation model - Ogochukwu Kelechi Onyeso; Adebiyi Boco; Md Kamrul Islam; Alexander Darku; Lars K. Hallstrom (International Journal of Adolescence and Youth)
The COVID-19 pandemic increased the prevalence of mental health disorders among youths. This study explored the association between COVID-19’s social and economic disruptions, mental health disorders, and coping behaviours among youths using Statistics Canada’s COVID-19 and Mental Health data. The study included 895 participants aged 18–24 years (52.9% women). Social and economic disruptions, healthy and unhealthy coping behaviours, and mental health severity (MHS) latent variables were delineated through exploratory factor analysis. Structural equation modelling revealed that social disruptions significantly increased the MHS (β = 0.77, p < 0.001), as well as healthy (β = 0.25, p < 0.001) and unhealthy (β = 0.54, p < 0.001) coping behaviours. Similarly, economic disruption was associated with an increase in healthy coping behaviours (β = 0.14, p = 0.043). Healthy coping behaviours (β=-0.08, p = 0.047) and positive coping skills (mastery) (β = -0.26, p < 0.001) were associated with a reduction in MHS. Positive coping behaviours mediated the social impact of COVID-19 on youth MHS; negative behaviours (substance use) had no significant mediation effect.